Menemukan Solusi Cerdas: Merumuskan Strategi Peningkatan Kinerja Karyawan KUA Berdasarkan Kajian Sistematis Literatur Review - Maulana, Ahmad Syahid Ridlo; Sunandar, Imam; Djuniardi, Dede (LPPM Institut Pendidikan Nusantara Global, 2024)
This systematic literature review research explains the leadership and motivation of employee performance in KUA. As a technical implementation unit under the directorate general of Islamic community guidance as stated in PMA 34 of 2016, KUA has served the daily lives of Indonesian people such as marriage, marriage guidance and zakat waqf. However, the performance of KUA employees is often faced with various challenges, such as lack of leadership and motivation. Optimal performance of KUA employees is the key to providing quality services to the community. This study aims to find smart solutions in formulating strategies to improve the performance of KUA employees based on a systematic review of leadership and motivation review literature. The study was conducted by collecting and analyzing literature related to factors that affect the performance of KUA employees, as well as effective strategies to improve the performance of the State civil apparatus (ASN) in the religious affairs office. The results showed that there are several factors that affect the performance of KUA employees, namely transformational leadership, charismatic leadership, intrinsic motivation, and extrinsic motivation. These factors are interrelated and can be optimized to improve the performance of KUA employees.